Molecular and histologic outcomes following spinal cord injury in spiny mice, Acomys cahirinus. Issue 9 (19th December 2019) - Streeter, Kristi A.; Sunshine, Michael D.; Brant, Jason O.; Sandoval, Aaron G. W.; Maden, Malcolm; Fuller, David D.
Abstract: The spiny mouse ( Acomys cahirinus) appears to be unique among mammals by showing little scarring or fibrosis after skin or muscle injury, but the Acomys response to spinal cord injury (SCI) is unknown. We tested the hypothesis that Acomys would have molecular and immunohistochemical evidence of reduced spinal inflammation and fibrosis following SCI as compared to C57BL/6 mice ( Mus ), which similar to all mammals studied to date exhibits spinal scarring following SCI. Initial experiments used two pathway‐focused RT‐PCR gene arrays ("wound healing" and "neurogenesis") to evaluate tissue samples from the C2–C6 spinal cord 3 days after a C3/C4 hemi‐crush injury (C3Hc). Based on the gene array results, specific genes were selected for RT‐qPCR evaluation using species‐specific primers. The results supported our hypothesis by showing increased inflammation and fibrosis related gene expression ( Serpine 1, Plau, and Timp1) in Mus as compared to Acomys ( p < .05). RT‐qPCR also showed enhanced stem cell and axonal guidance related gene expression (Bmp2, GDNF, and Shh) in Acomys compared to Mus ( p < .05). Immunohistochemical evaluation of the spinal lesion at 4 weeks postinjury indicated less collagen IV immunostaining in Acomys ( p < .05). Glial fibrillary acidic protein (GFAP) and ionized calcium binding adaptor molecule 1(IBA1) immunostaining indicated morphological differences in the appearance of astrocytes and macrophages/microglia in Acomys . Collectively, the molecular and histologic results support the hypothesis that Acomys has reduced spinal inflammation and fibrosis following SCI. We suggest that Acomys may be a useful comparative model to study adaptive responses to SCI. Abstract : We tested the hypothesis that the spiny mouse ( Acomys cahirinus ) would have molecular and immunohistochemical evidence of reduced spinal inflammation and fibrosis following spinal cord injury (SCI) as compared to C57BL/6 mice ( Mus ). Based on initial gene array results of the local response to SCI, specific genes were selected for RT‐qPCR using species‐specific primers. The results showed increased inflammation and fibrosis related gene expression in Acomys as compared to Mus . Immunohistochemical evaluation of the spinal lesion indicated reduced collagen IV immunostaining in Acomys . Collectively, the results support the hypothesis that Acomys has reduced spinal inflammation and fibrosis following SCI. Acomys may be a useful comparative model to study adaptive responses to SCI.